2012
DOI: 10.1002/etc.1744
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a new battery of toxicity tests for boreal forest soils: Assessment of the impact of hydrocarbons and salts

Abstract: The ability to assess the toxic potential of soil contamination within boreal regions is currently limited to test species representative of arable lands. This study evaluated the use of six boreal plant species (Pinus banksiana, Picea glauca, Picea mariana, Populus tremuloides, Calamagrostis Canadensis, and Solidago canadensis) and four invertebrate species (Dendrodrilus rubidus, Folsomia nivalis, Proisotoma minuta, and Oppia nitens) and compared their performance to a suite of standard agronomic soil test sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
18
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 34 publications
2
18
0
Order By: Relevance
“…With a maximum life span of 140 d and a large average clutch size per adult, F. candida represents an opportunistic species that invests energy into reproduction rather than survival, as is apparent by their relatively tolerant reproductive response to petroleum hydrocarbon–contaminated soils (van Straalen ; Rubach et al ; Environment Canada ). Based on our findings and other studies on earthworm reproduction (Cermak et al ; Agnell et al ; Princz et al ), the reproduction of mites and earthworms was sensitive to petroleum hydrocarbon–contaminated soils. Their life history traits reflect the fact that they allocate more energy to survival than reproduction (Murphy and Sardar ; Environment Canada 2004; Norton and Behan‐Pelletier ; Princz et al ).…”
Section: Discussionsupporting
confidence: 84%
“…With a maximum life span of 140 d and a large average clutch size per adult, F. candida represents an opportunistic species that invests energy into reproduction rather than survival, as is apparent by their relatively tolerant reproductive response to petroleum hydrocarbon–contaminated soils (van Straalen ; Rubach et al ; Environment Canada ). Based on our findings and other studies on earthworm reproduction (Cermak et al ; Agnell et al ; Princz et al ), the reproduction of mites and earthworms was sensitive to petroleum hydrocarbon–contaminated soils. Their life history traits reflect the fact that they allocate more energy to survival than reproduction (Murphy and Sardar ; Environment Canada 2004; Norton and Behan‐Pelletier ; Princz et al ).…”
Section: Discussionsupporting
confidence: 84%
“…In a study with petroleum hydrocarbon‐contaminated soil (~250 000 mg/kg total petroleum hydrocarbon), Princz et al () found no mortality of O. nitens ; however, they observed that reproduction was substantially impacted relative to control. Gainer et al () assessed the toxicity of lubricating oil, a 50/50 mixture of F2/F3 petroleum hydrocarbons, to O. nitens in OECD artificial soil (10% peat) and reported a reproduction EC50 value of 1210 mg/kg.…”
Section: O Nitens In Soil Ecotoxicologymentioning
confidence: 99%
“…This study focuses on the isolation, characterization and selective stimulation of cold‐ and salt‐tolerant hydrocarbon‐degrading bacteria particularly for the biostimulation of petroleum‐contaminated sub‐Arctic soils abruptly impacted by sources of high salinity (such as saline industrial effluents). Hydrocarbon‐ and salt‐contaminated soils often exist at drilling waste disposal sites and abandoned flare pits in oil and gas fields located in cold, remote areas of northern Canada and other cold‐region countries …”
Section: Introductionmentioning
confidence: 99%